2020
DOI: 10.3389/fphar.2020.00638
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Genetic Admixture Components on CYP3A5*3 Allele-Associated Hypertension in Amerindian Populations From Northwest Mexico

Abstract: safer drug administration regimens, assuring better therapeutic responses and fewer side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
3
3
0
Order By: Relevance
“…According to our results, the CYP3A5*3 allele seems to be predominant in the Chilean population, which could be due in part to the genetic structure of Chileans as a consequence of the admixture between Native Amerindians, the historical migration of individuals from Europe and, to a lesser extent, the arrival of African individuals ( Eyheramendy et al, 2015 ). Similar results have been observed in other admixed Latin American populations in terms of the presence of the three CYP3A5 genotypes, the association with different TAC pharmacokinetic patterns and the influence of ancestry ( Ferraris et al, 2011 ; Cusinato et al, 2014 ; Galaviz-Hernández et al, 2020 ). GWAS studies in North American, Caucasian, African and Asiatic populations have validated the role of CYP3A5 as the main predictor of TAC metabolism, although a few other common variants in cytochrome P450 enzymes and drug transporters have been suggested as contributing to the variability in plasma drug levels ( Oetting et al, 2018 ; Bruckmueller et al, 2015 ; Oetting et al, 2016 ).…”
Section: Discussionsupporting
confidence: 87%
“…According to our results, the CYP3A5*3 allele seems to be predominant in the Chilean population, which could be due in part to the genetic structure of Chileans as a consequence of the admixture between Native Amerindians, the historical migration of individuals from Europe and, to a lesser extent, the arrival of African individuals ( Eyheramendy et al, 2015 ). Similar results have been observed in other admixed Latin American populations in terms of the presence of the three CYP3A5 genotypes, the association with different TAC pharmacokinetic patterns and the influence of ancestry ( Ferraris et al, 2011 ; Cusinato et al, 2014 ; Galaviz-Hernández et al, 2020 ). GWAS studies in North American, Caucasian, African and Asiatic populations have validated the role of CYP3A5 as the main predictor of TAC metabolism, although a few other common variants in cytochrome P450 enzymes and drug transporters have been suggested as contributing to the variability in plasma drug levels ( Oetting et al, 2018 ; Bruckmueller et al, 2015 ; Oetting et al, 2016 ).…”
Section: Discussionsupporting
confidence: 87%
“…Consequently, CYP3A5 gene expression showed higher expression in Vervet females compared to males, although this change was not significant (p = 0:09, difference = − 0:4171 ± 0:2346) (Figure 2). This was correlated to the previous studies in the human population, which showed that the CYP3A5 gene is significantly higher in females than in males [40,41].…”
Section: Discussionsupporting
confidence: 90%
“…8 A recent study evaluated the frequency of the rs776746 polymorphism and its association with hypertension in eight indigenous populations from Mexico. 53 The analysis report that the CYP3A5*3/*3 genotype frequencies ranged from 23.5% in Mexicaneros to 93.3% in Mayos, and the mean observed in the Mexican indigenous groups was 67.5% (very similar to the frequency found in the Native Americans of our study). Also, Galaviz-Hernandez et al found that the CYP3A5*3/*3 genotype was more frequent in indigenous women with higher systolic and diastolic blood pressures values.…”
Section: Cyp3a5supporting
confidence: 87%